Pengaruh Pengetahuan Gizi Ibu Dan Sosial Ekonomi Keluarga Terhadap Status Gizi Balita Umur 6-24 Bulan Di Wilayah Kerja Puskesmas Tamalanrea Jaya - Hertien Novi Roficha; Fatmawaty Suaib; Hendrayati Hendrayati (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
Mothers’ nutritional knowledge play an important role in nutritional status of children since mothers have responsibility to provide food for family, particularly for children. Although mothers have good knowledge in nutrition, but if their level of socioeconomic is low, it will affect to nutritional status of children.The aim of this research is to determine effect of mothers’ nutritional knowledge and socioecomic family on nutritional status of children aged 6 to 24 months at Tamalanrea Jaya public health center. The kind of this research is analityc research. Sample consists of 69 children aged 6 to 24 months and their mother are the respondents who are chosen by purposive sampling. The effect of variable is detected by chi-squared test and data is demonstrated by table and narration.Result of this research shows that there are influence of mothers’ nutritional knowledge and parents revenue with nutritional status of children aged 6 to 24 months which are explained by p-value = 0.002 < α = 0.05 and p-value = 0.026 < α = 0.05 respectively. However, level of mothers’ education and mothers’ job did not have influence to nutritional status of children aged 6 to 24 months which are proved by p-value = 0.587 > α = 0.05 and p-value = 0.69 > α = 0.05 respectively.This research is suggestible to mothers to improve their knowledge in nutritional problem by following nutritional counselling or reading nutrition books for increasing insight about nutritional problem